Shifting alpine plant distributions with global change: Testing the environmental matching hypothesis - Clifton P. Bueno de Mesquita; Sarah C. Elmendorf; Jane G. Smith; Katharine N. Suding (Arctic, Antarctic, and Alpine Research)
Species facing novel temperature, precipitation, and nitrogen (N) deposition regimes must move or adapt to persist. For long-lived plants, a primary form of climate acclimation is through shifting geographic range limits or establishing in favorable microclimates. One commonly assumed but rarely tested hypothesis is that these shifts can be predicted by environmental matching: that the environmental characteristics that define a current distribution should predict how a population will shift with environmental changes. To test this hypothesis, we transplanted four alpine and two subalpine plant species into environments with experimentally increased temperature, snow, and N. We predicted that species would perform best when environmental change matched their geographic distributional characteristics: increased temperature, snow, and N (two subalpine species), increased temperature (two dry meadow specialists), and increased snow (two snowbed specialists). Our results provided limited support for the environmental matching hypothesis. Snowbed specialists did not benefit from increased snow, dry meadow specialists' performance did not consistently differ among the treatments, and subalpine plants' survival was not affected by treatments while their growth response was variable among species. Our results suggest that global change effects will vary among species and distributional shifts are not easily predicted by species environmental preference.